2018
DOI: 10.1177/2041731418790694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface topography and coating on osteogenesis and bacterial attachment on titanium implants

Abstract: Titanium (Ti) plays a predominant role as the material of choice in orthopaedic and dental implants. Despite the majority of Ti implants having long-term success, premature failure due to unsuccessful osseointegration leading to aseptic loosening is still too common. Recently, surface topography modification and biological/non-biological coatings have been integrated into orthopaedic/dental implants in order to mimic the surrounding biological environment as well as reduce the inflammation/infection that may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 159 publications
(151 reference statements)
0
110
0
Order By: Relevance
“…55,56 The results of the studies reported herein demonstrate that osteogenesis may be partially due to the rough topography of LOG nanoparticles, further supported by published studies. [57][58][59][60][61][62]…”
Section: Discussionmentioning
confidence: 99%
“…55,56 The results of the studies reported herein demonstrate that osteogenesis may be partially due to the rough topography of LOG nanoparticles, further supported by published studies. [57][58][59][60][61][62]…”
Section: Discussionmentioning
confidence: 99%
“…The unique bactericidal properties of cicada and dragonfly wings have drawn significant research interest [7][8][9][10] , as the physical nature of bacterial killing could provide an effective strategy to prevent biofilm formation, and infection of indwelling and implantable devices, while negating the current need to use materials impregnated with antibiotics. To date, a wide range of nanofabrication techniques have been utilised to generate bactericidal nanotopographies on synthetic materials, including black silicon (bSi) 2 , titanium 11 , titanium alloy 12 and polymers 13 .…”
mentioning
confidence: 99%
“…In the past two decades, many efforts, mainly on the industrial side, have been made to overcome this possible shortcoming and improve bio-integration, especially osseointegration. For example, the titanium surface has been modified micro-topographically or chemically by etching, blasting, ultraviolet (UV) ray irradiation, atmospheric pressure plasma (APP) treatment, and many other methods [4][5][6][7][8][9][10]. Furthermore, hybridization techniques with other materials, such as calcium phosphates, were recently introduced to improve the bio-affinity of implants to bone.…”
Section: Introductionmentioning
confidence: 99%